Analysis of new situations for quasiconvexity versus rank-one convexity in 2 x 2 and other dimensions - Bandeira, Luís Miguel Zorro (2014)
It is well-known that quasiconvexity is a fundamental concept for vector problems in the Calculus of Variations. Its main necessary condition is rankone convexity. Still today it is not known whether it is also sufficient or not, when the target space of deformations is m=2 (in the general case). We introduce a method to find, in a systematic way, rank-one convex polynomials. We show how it works in several examples. It can also be applied to convexity along general cones. An alternative proof is provided for the well-known quadratic case of quasiconvexity, which does not use the Plancherel formula. An application to the case of 4th degree homogeneous polynomials is shown. We also explore an attempt to disprove the implication, from rank-one convexity to quasiconvexity for 2x2 symmetric matrices, using the viewpoint of laminates and homogeneous gradient Young measures. /RESUMO - É bem conhecido que a quasiconvexidade é um conceito fundamental para problemas vectoriais do Cálculo das Variações. A sua principal condição necessária é a convexidade característica-l. Ainda hoje não é conhecido se é ou não suficiente, quando o espaço alvo das deformações é m=2 (no caso geral). Introduzimos um método para determinar, de uma forma sistemática, polinómios convexos característica-1. Mostramos como funciona em diversos exemplos. Pode também ser aplicado à convexidade ao longo de cones gerais. Providenciamos uma demonstração alternativa para o bem conhecido caso quadrático da quasiconvexidade, que não utiliza a fórmula de Plancherel. Apresentamos uma aplicação para o caso dos polinómios homogéneos de grau 4. Exploramos também uma tentativa para refutar a implicação da convex-idade característica-1 para a quasiconvexidade nas matrizes 2x2 simétricas, sob o ponto de vista dos laminados e das medidas de Young gradiente homogéneas.